New Insights into the Role of MHC Diversity in Devil Facial Tumour Disease - Lane, Amanda (Public Library of Science, 2012)
BACKGROUND: Devil facial tumour disease (DFTD) is a fatal contagious cancer that has decimated Tasmanian devil populations. The tumour has spread without invoking immune responses, possibly due to low levels of Major Histocompatibility Complex (MHC) diversity in Tasmanian devils. Animals from a region in north-western Tasmania have lower infection rates than those in the east of the state. This area is a genetic transition zone between sub-populations, with individuals from north-western Tasmania displaying greater diversity than eastern devils at MHC genes, primarily through MHC class I gene copy number variation. Here we test the hypothesis that animals that remain healthy and tumour free show predictable differences at MHC loci compared to animals that develop the disease. METHODOLOGY/PRINCIPAL FINDINGS: We compared MHC class I sequences in 29 healthy and 22 diseased Tasmanian devils from West Pencil Pine, a population in north-western Tasmania exhibiting reduced disease impacts of DFTD. Amplified alleles were assigned to four loci, Saha-UA, Saha-UB, Saha-UC and Saha-UD based on recently obtained genomic sequence data. Copy number variation (caused by a deletion) at Saha-UA was confirmed using a PCR assay. No association between the frequency of this deletion and disease status was identified. All individuals had alleles at Saha-UD, disproving theories of disease susceptibility relating to copy number variation at this locus. Genetic variation between the two sub-groups (healthy and diseased) was also compared using eight MHC-linked microsatellite markers. No significant differences were identified in allele frequency, however differences were noted in the genotype frequencies of two microsatellites located near non-antigen presenting genes within the MHC. CONCLUSIONS/SIGNIFICANCE: We did not find predictable differences in MHC class I copy number variation to account for differences in susceptibility to DFTD. Genotypic data was equivocal but indentified genomic areas for further study.